Tuning thermal expansion from strong negative to zero to positive in Cu2-xZnxP2O7 solid solutions. (15th January 2022) - Shi, Naike; Sanson, Andrea; Venier, Alessandro; Fan, Longlong; Ren, Yang; de Souza, Danilo Oliveira; Olivi, Luca; Song, Yuzhu; Xing, Xianran; Chen, Jun
Abstract: Chemical substitution is an effective strategy to control the thermal expansion properties in solid solutions. In this work, a series of solid solutions Cu2- x Zn x P2 O7 (0 ≤ x ≤ 2) were synthesized by solid state reaction methods. The thermal expansion in Cu2- x Zn x P2 O7 is tuned from strong negative thermal expansion ( αv ∼ -33.5×10 −6 K −1, 100 - 375K) to near zero thermal expansion ( αv ∼ -2.78×10 −6 K −1, 100 - 225K), and then to positive thermal expansion gradually with increasing content of Zn 2+ substitution. The direct experiment results reveal that the Zn 2+ substitution diminishes the rigidity of Cu/Zn-O and P-O bonds and the transverse vibrations of O atoms arousing negative thermal expansion. The present work achieves the regulation of thermal expansion from negative to near zero and finally to positive in the Cu2 P2 O7 system. Graphical abstracts: Image, graphical abstract